Alternative Narratives in History Learning for Multicultural Education in Indonesia - Sohabudin, Ahmad; Darmawan, Wawan (Universitas Negeri Semarang, 2023)
Indonesia is currently experiencing symptoms of strengthening identity politics. As a pluralistic nation, this phenomenon is dangerous because it can lead to social conflict and national disintegration. This research was conducted with the aim that educational institutions can play a role in minimizing this potential. What he can do is instill the values of multiculturalism in learning practices, especially in history learning. For this reason, the problems that are tried to be put forward in this research are: 1) what is meant by multiculturalism education? 2) what is the conception of multiculturalism education in history learning? 3) how can a multiculturalism narrative be developed in history learning materials? This research uses a literature study method. The literature study obtained data from several library sources such as journal articles, books, the internet, newspapers, and magazines. The study revealed that multiculturalism education is a concept created to help someone understand and appreciate regardless of the high or low culture, ethnicity, religion, race, gender, language, economic ability, or disability inherent in a person. Learning history with a multiculturalism approach is ideological. In history learning, multiculturalism education can be carried out by accommodating students' cultural differences, utilizing culture as a source of content, and using history as a tool to understand other people's cultures in order to grow mutual respect, tolerance, a sense of unity and the spirit of nationalism. A historical event that can be used as an alternative narrative in the development of multiculturalism education is when Suharto, at the beginning of his reign, tried to re-establish Pancasila and the 45' constitution as the ideology and basis of the state amid the threat of ideological conflicts between political parties and the emergence of an inclusive Islamic movement led by Nurcholish Madjid as a response to the death of the movement Islamic politics during the Orde Baru era.